La progettazione partecipata negli interventi di recupero urbano - DOI: 10.5752/P.2316-1752.2009v16n18/19p203 - Michelini, Anna Conigliaro (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract Key words : Participation; Urban settlement upgrading; Town planning.Since the decline of State leadership in the 90s within the scope of urban policies aimed at solving problems resulting from informal settlements through urban planning as a prescriptive tool, one cannot ignore the fundamental participation of communities concerned with settlement upgrading projects in urban areas informally occupied as sites of “the beginning of the solution.” This paper attempts to define and draw the main methodological lines of the participatory process in urban settlement upgrading projects, referring to the most significant experiences implemented up to now.